Microbiology a systems approach - Cowan, M. Kelly
"This book is suited for all kinds of students and doesn't require any prerequisite knowledge of biology or chemistry. If you are interested in entering the health care profession in some way, this book will give you a strong background in the biology of microorganisms without overwhelming you with unnecessary details. Don't worry if you're not in the health professions. A grasp of this topic is important for everyone - and can be attained with this book"--Provided by publisher.